Status Nutrisi dan Hemoglobin Setelah Pemberian Transfusi pada Penderita Thalasemia - Dwiyanti Purbasari; Erida Fadila; Meli Nur Imani (Jurnal Medika Nusantara, 2023)
More than 5,000 babies are born suffering  thalassemia (beta thalassemia major and beta thalassemia Hb E) annually from around the world and 80% of births occur in developing countries (Kantharaj & Chandrashekar, 2018). In Indonesia alone, the frequency of beta thalassemia genes ranges from 3-10% with 2,500 babies born each year and there are 10,531 more patients experiencing thalassemia (Kemenkes, 2019). The general objective of this study was to identify the relationship between nutritional status and changes in hemoglobin levels after transfusion in children with thalassemia at RSD Gunungjati Cirebon. This research method uses descriptive correlation by using a cross sectional. The sample of this research is thalassemia in Gunung Jati Hospital, Cirebon City, totaling 35 respondents using  accidental sampling technique. The instrument used is a data and measurement recapitulation sheet. The nutritional status data recapitulation sheet containing components (gender, age, weight, TB) and measurement of Hb before and after blood transfusion using EasyTouch GCHB, as well as data analysis using the Spearman rank, was carried out on July 4-15, 2022. The results of the univariate analysis of the study This is in the category of good nutritional status as many as 18 respondents (51.4%) and an increase in hemoglobin levels of 18 respondents (51.4%) in thalassemia children at Gunungjati Hospital, Cirebon. The results of this study found that there was no relationship between nutritional status and changes in hemoglobin levels in thalassemia children at RSD Gunungjati Cirebon with a value (p = 0.252 > = 0.05).Suggestions for this study are that families and patients should strive to carry out the education provided by nurses and explore more knowledge related to thalassemia, especially nutritional intake.